Micronuclei and nuclear anomalies in Mexico's indigenous population - Blanca Patricia Lazalde-Ramos; Ana Lourdes Zamora-Pérez; Martha Sosa-Macías; Carlos Galaviz-Hernández; Guillermo Moisés Zúñiga-González (Instituto Nacional de Salud Pública, 2017)
Objective. To determine the number of micronuclei and nuclear anomalies in Mexico's indigenous population. Materials and methods. One hundred twenty indigenous individuals were evaluated, including thirty from the ethnicities Cora, Huichol, Tarahumara and Tepehuano. The number of micronuclei (MN) and any nuclear abnormality (NA) in oral mucosa cells, including cells with nuclear buds, binucleated cells, cells with karyolysis, karyorrhetic, condensed chromatin and pyknotic cells were determined for each participant. Results. Tepehuano and Tarahumaras showed the greatest damage to DNA. The Tepehuano group presented the highest number of MN and NA, this being a significant difference (p < 0.05) compared with the rest of the studied groups. This group also presented the highest herbicide exposure (46.7%). In relation to the smoking and drinking habits, these were more frequent in the Tarahumara group (33.3 and 50% respectively). Conclusion. The ethnic diversity, habits and customs may influence the DNA nuclear integrity in the Amerindian groups.